The Impact of Prescribed Exercise and Short-Term Caloric Restriction on Moderate-to-Vigorous Physical Activity (P08-011-19). (24th October 2019) - Martin, Alexandra; Wallmann-Sperlich, Birgit; Sperlich, Billy; Koehler, Karsten
Abstract: Objectives: Weight loss, especially when achieved by caloric restriction (CR), reduces total daily energy expenditure (EE), which can attenuate further weight loss. Although exercise is a common countermeasure to the decline in EE, it is unknown whether prescribed exercise leads to compensatory changes in moderate-to-vigorous physical activities (MVPA) during non-exercise periods in the context of CR. The present study sought to quantify changes in MVPA in response to an energetically-matched energy deficit induced by CR alone or combined with exercise. We hypothesized that MVPA outside of prescribed exercise would be greater during non-exercise conditions, regardless of energy balance. Methods: In a repeated-measures crossover design, active men ( n  = 6, 25 ± 1.0 y) underwent four 4-day conditions: CR with exercise (CR + X), CR without exercise (CR–X), energy-balanced control (CON) with exercise (CON + X) and without exercise (CON–X). Dietary intake was manipulated such that energy availability (EA) was 15 kcal·kg FFM −1 ·day −1 (CR) or 40 kcal·kg FFM −1 ·day −1 (CON). Prescribed exercise EE was 15 kcal·kg FFM −1 ·day −1 . Physical activity was assessed using the SenseWear Pro3 armband (Bodymedia, Pittsburgh, USA) to quantify time spent in MVPA and light activities (sleep, lying down without sleep, and non-lying light activities) as % of total wear time. Results: EA did not differ between CR ( P  = 0.87) nor CON ( P  = 0.42). As expected, weight loss was significant ( P  < 0.001) in CR + EX (–1.8 ± 0.4 kg) and CR-EX (–2.4 ± 0.3 kg). After deducting prescribed exercise, there was a significant effect of exercise on time spent in MVPA ( P  = 0.02), in that MVPA was lower during CON-EX vs. CON + EX (11.4 ± 2.0% vs. 17.9 ± 2.1%, P  = 0.03) and trended lower during CR-EX vs. CR + EX (13.6 ± 1.5% vs. 15.5 ± 1.6%, P  = 0.08). In exercise conditions, MVPA was lower during CR + EX when compared to CON + EX ( P  = 0.03). Conclusions: Independent of energy balance, engaging in short-term exercise led to more, not less, time spent in non-exercise MVPA. These findings indicate the prevention of reductions in non-exercise activity as an additional benefit of incorporating exercise into weight loss interventions. Funding Sources: The study was supported in part by the USDA National Institute of Food and Agriculture and institutional funding from the University of Nebraska-Lincoln.